Molecular cytological characterization of two novel durum –Thinopyrum intermedium partial amphiploids with resistance to leaf rust, stem rust and Fusarium head blight. Issue 1 (21st February 2013) - Zeng, J.; Cao, W.; Fedak, G.; Sun, S.; Mccallum, B.; Fetch, T.; Xue, A.; Zhou, Y.
<x xml:space="preserve">Abstract</x> Thinopyrum intermedium, a wild relative of wheat, is an excellent source of disease resistance. Two novel partial amphiploids, 08‐47‐50 and 08‐53‐55 (2n = 6x = 42), were developed from wide crosses between durum wheat and Th. intermedium. Meiotic analysis showed that pollen mother cells of the two partial amphiploids formed an average 20.49 bivalents for 08‐47‐50 and 20.67 bivalents for 08‐53‐55, indicating that they are basically cytologically stable. GISH analysis revealed that the two partial amphiploids carried different chromosome compositions. 08‐47‐50 had fourteen chromosomes from Th. intermedium and its alien chromosomes included six St‐, four Ee‐ and four Ee‐St translocated chromosomes, whereas 08‐53‐55 had four St‐ and ten Ee‐St translocated chromosomes. Fungal disease evaluation indicated that both partial amphiploids had a high level of resistance to FHB, leaf rust and stem rust race Ug99. These two novel partial amphiploids with multiple disease resistance could be used as a new source of multiple disease resistance in bread wheat and durum wheat breeding programs.